Design and characterization of kinetic inductance detectors for the next-generation OLIMPO experiment - Cacciotti, Federico; Paiella, Alessandro; Avestruz, Camille; Basu Thakur, Ritoban; Battistelli, Elia S.; de Bernardis, Paolo; Bulbul, Esra; Columbro, Fabio; Coppolecchia, Alessandro; Cray, Scott; D'Alessandro, Giuseppe; De Petris, Marco; et al. (Millimeter, Submillimeter, and Far-Infrared Detectors and Instrumentation for Astronomy XII, 2024)
OLIMPO is a 2.6m balloon–borne telescope intended to observe, with high–angular resolution, the millimeter and sub–millimeter sky from the Antarctic stratosphere. It will allow us to study the dynamics of galaxy cluster formation and to characterize the intergalactic medium up to the cluster outskirt through the Sunyaev-Zel’dovich effect. OLIMPO utilizes four arrays of kinetic inductance detectors (KIDs), in the 145, 250, 350 and 460 GHz bands, operated at about 300 mK. OLIMPO has already flown, in a technological flight, in 2018 from Svalbard, Norway, proving for the first time that KIDs are capable to withstand the demanding conditions on high altitude balloons. KIDs are superconducting, low–temperature detectors suited for this kind of applications due to their intrinsic capability to be frequency–domain multiplexed, enabling very high–sensitivity sky surveys. In this work, we present the design, optimization and laboratory characterization of the 313–pixel array for the OLIMPO 350 GHz frequency band. We showcase results of the electrical characterization (electrical responsivity and the measurement of the quasiparticle lifetime) and the optical characterization (optical responsivity and optical efficiency) accomplished with a 4 K cooled black body